Battery and electric equipment

By overlapping the first adhesion of the adhesive parts in the battery pole film, the first adhesive part of the adhesive part and the polar thinning area are overlapped, and it is set to a single -sided glue to solve the problem of lithium analysis of lithium and falling when the battery pole slice is thin. The cycle performance of the battery and anti -falling performance.

CN119381514AActive Publication Date: 2025-01-28NINGDE AMPEREX TECHNOLOGY LTD

Patent Information

Application Number
CN202411547230.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-01-28
Estimated Expiration
2044-10-31

AI Technical Summary

Technical Problem

The thinned area of ​​the battery pole plate is prone to lithium extraction during the cycle, which affects the circulation performance and safety of the battery cell. At the same time, the battery is prone to squirting when it falls or shakes, resulting in the risk of shell damage and short circuit.

Method used

Design a battery, including the shell, electrode component and adhesion. The polar chip of the electrode component is stacked along the thickness direction. The polar sheets include the stream and the active substance layer. At least part of the thinning area of ​​the first adhesion and the polar sheet is at least partially overlap. The first adhesion is set to a single -sided glue to reduce the effect of the pull between the adhesive and the shell on the pole.

Benefits of technology

By reducing the increase in the risk of gap between adjacent polar sections, improving marginal lithium, improving the cycle performance of the battery, and enhancing the resistance of the battery's anti -falling performance, reducing the risk of moving and short -circuit.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119381514A_ABST
    Figure CN119381514A_ABST
Patent Text Reader

Abstract

The invention discloses a battery and electric equipment. The battery comprises a shell, an electrode assembly and a bonding piece, the electrode assembly is contained in the shell and comprises multiple layers of pole pieces arranged in a stacked mode in the first direction, each pole piece comprises a main body area and a thinning area, and the thickness of each thinning area is smaller than that of the main body area. The electrode assembly comprises a first surface, and the area, overlapped with the thinning area in the first direction, of the first surface is a first area. The shell and the first surface are bonded through the bonding piece, the bonding piece comprises a first bonding piece, the first bonding piece and the first area are at least partially overlapped, and the first bonding piece comprises a first base material and a first bonding layer which are arranged in a stacked mode in the first direction. In the first direction, the surface, away from the first bonding layer, of the first base material covers part of the first surface, and the surface, away from the first base material, of the first bonding layer is bonded with part of the shell; or in the first direction, the surface, away from the first base material, of the first bonding layer is bonded with part of the first surface, and the surface, away from the first bonding layer, of the first base material covers part of the shell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a battery and an electrical device. Background Art

[0002] Rechargeable batteries (such as lithium-ion batteries) are widely used in electric vehicles and consumer electronics due to their advantages such as high energy density, high output power, and long cycle life. The safety performance of rechargeable batteries is of concern to the public.

[0003] During the production of battery pole pieces, the active material layer slurry is fluid when it is not solidified. A thinning area will be formed at the junction of the active material layer and the empty foil area due to the natural leveling of the active material layer slurry. The thickness of the edge thinning area is less than the normal area in the middle. The thinning area at the edge of the pole piece is located at the head of the battery cell after winding or lamination, that is, the side where the pole ear extends out. After multiple layers of accumulation, the thickness at the head of the battery cell is less than the thickness in the middle of the battery cell. Due to the existence of the thinning area, the pole piece at the head of the battery cell has a gap between the positive and negative electrodes, which is prone to abnormalities such as lithium deposition during the cycle process, seriously affecting the cycle performance and safety of the battery cell.

[0004] When a battery falls or shakes, the cells inside it are prone to move and impact the battery shell, causing the shell to be damaged and leaking. The diaphragm may also shrink, resulting in a short circuit, affecting safety. Adhesives are usually used to bond the cells and shell to fix the cells and shell relatively, preventing the cells from moving under conditions such as falling, thereby improving safety performance. However, there is a pulling force between the adhesive and the shell, which pulls the outermost electrode to increase the gap between the positive and negative electrodes, worsening lithium deposition. Summary of the invention

[0005] One purpose of the application is to propose a battery and electrical equipment that can improve the problem of lithium deposition in the thinned area of ​​the electrode.

[0006] The first aspect of the present application provides a battery, comprising a shell, an electrode assembly and an adhesive. The electrode assembly is contained in the shell, and the electrode assembly comprises a plurality of electrode sheets stacked along a first direction, and the first direction is the thickness direction of the electrode sheets; the electrode sheets comprise a current collector and an active material layer, and the active material layer is disposed on at least one surface of the current collector; the active material layer comprises a main region and a thinning region, and in the first direction, the average thickness of the main region is T3, and the average thickness of the thinning region is T4, and T3>T4; the electrode assembly comprises a first surface facing the shell, and the region of the first surface overlapping with the thinning region in the first direction is the first region. The adhesive adheres the shell and the first surface, and the adhesive comprises a first adhesive, and along the first direction, the first adhesive at least partially overlaps with the first region, and the first adhesive comprises a first substrate and a first adhesive layer stacked along the first direction. Along the first direction, the surface of the first substrate away from the first adhesive layer covers part of the first surface, and the surface of the first adhesive layer away from the first substrate adheres to part of the shell; or, along the first direction, the surface of the first adhesive layer away from the first substrate adheres to part of the first surface, and the surface of the first substrate away from the first adhesive layer covers part of the shell.

[0007] The battery provided in the present application is configured with a first adhesive that at least partially overlaps with the thinned area of ​​the pole piece, and the first adhesive covers a portion of the first surface and is bonded to the shell, or the first adhesive covers a portion of the shell and is bonded to the first surface, that is, the first adhesive is configured as a single-sided adhesive, so that the pulling force generated between the adhesive and the shell is not easy to directly act on the thinned area, thereby reducing the risk of increased gaps between the thinned areas of adjacent pole pieces, improving edge lithium plating, and improving cycle performance.

[0008] Based on the first aspect, in some possible implementations, the material of the first substrate includes one or more of polyethylene terephthalate, polyimide, polyethylene, polypropylene, polyvinyl chloride, kraft paper, cotton cloth, synthetic fiber cloth, metal foil, and glass fiber; the material of the first bonding layer includes one or more of rubber-based adhesives, silicone-based adhesives, hot melt adhesives, water-based adhesives, polyurethane-based adhesives, epoxy-based adhesives, and polyimide-based adhesives.

[0009] Based on the first aspect, in some possible implementations, the electrode assembly further includes an electrode terminal, the extension direction of the electrode terminal is a second direction, and the second direction is perpendicular to the first direction; along the second direction, the width of the area where the first adhesive overlaps with the first area is W, and the width of the thinned area is W1, 0.7≤W / W1≤1.1. When W / W1≥0.7, the first adhesive has a certain width in the first area, which can reduce the increase in the gap between the thinned areas of adjacent pole pieces caused by the pulling force between the adhesive and the shell, and is conducive to increasing the thickness consistency of the thinned area and the main area in the second direction, and reducing the risk of lithium deposition in the thinned area due to undervoltage; by limiting the upper limit value of W / W1 to 1.1, the risk of the electrode assembly moving in the shell due to the large area of ​​the single-sided adhesive is reduced, the anti-drop performance of the battery is improved, and at the same time, the phenomenon of overvoltage in the main area due to the large overlapping area of ​​the first adhesive and the main area is reduced. Overvoltage will increase the risk of poor electrolyte infiltration in the main area and increase the risk of lithium deposition in the main area.

[0010] Based on the first aspect, in some possible implementations, 0.8≤W / W1≤1.0, which has a better effect of reducing lithium plating and improving drop resistance performance.

[0011] Based on the first aspect, in some possible implementations, the area of ​​the first surface that overlaps with the main area in the first direction is the second area, the adhesive also includes a second adhesive, along the first direction, the second adhesive at least partially overlaps with the second area, the second adhesive includes a second substrate, a second adhesive layer and a third adhesive layer stacked along the first direction, the second adhesive layer and the third adhesive layer are arranged on two surfaces of the second substrate opposite to each other along the first direction, the surface of the second adhesive layer away from the second substrate is bonded to the shell, and the surface of the third adhesive layer away from the second substrate is bonded to the first surface. The second adhesive is arranged in the second area overlapping with the main area, and the second adhesive is arranged as a double-sided adhesive, one side is bonded to the second area and the other side is bonded to the shell, which will improve the drop resistance of the electrode assembly, and the second adhesive can reduce the risk of undervoltage in the main area and reduce the risk of lithium deposition in the main area.

[0012] Based on the first aspect, in some possible implementations, the electrode assembly also includes an electrode terminal, the extension direction of the electrode terminal is the second direction, and the third direction is perpendicular to the first direction and the second direction in pairs; observed from the first direction, the first adhesive includes a first edge and a second edge relatively arranged along the third direction, the second adhesive includes a third edge and a fourth edge relatively arranged along the third direction, and the projection area of ​​the electrode assembly along the first direction includes a fifth edge and a sixth edge relatively arranged along the third direction; along the third direction, the fifth edge, the first edge, the second edge, and the sixth edge are arranged in sequence; along the third direction, the fifth edge, the third edge, the fourth edge, and the sixth edge are arranged in sequence; the distance between the first edge and the fifth edge along the third direction is L1, the distance between the second edge and the sixth edge along the third direction is L2, the distance between the third edge and the fifth edge along the third direction is L3, and the distance between the fourth edge and the sixth edge along the third direction is L4; 0≤|L1-L2|≤4mm, and / or, 0≤|L3-L4|≤4mm. The above-mentioned limitation ensures that the first adhesive and / or the second adhesive will not be too offset in the third direction relative to the electrode assembly. When the first adhesive and / or the second adhesive is offset too much in the third direction, the risk of uneven force on the electrode assembly in the third direction will increase, affecting the anti-drop performance of the electrode assembly.

[0013] Based on the first aspect, in some possible implementations, along the third direction, the length of the first adhesive is W2, the width of the second adhesive is W3, the width of the projection area of ​​the electrode assembly along the first direction is W4, 0.5≤W2 / W4≤1, and / or, 0.5≤W3 / W4≤1, which is beneficial to improving lithium plating and drop performance.

[0014] Based on the first aspect, in some possible implementations, 0.6≤W2 / W4≤0.8, and / or, 0.6≤W3 / W4≤0.8, the effect of improving lithium plating and drop performance is better.

[0015] Based on the first aspect, in some possible implementations, W2>W3. The width of the first adhesive in the second direction is generally smaller than the length of the second adhesive in the second direction. The probability of bubbles appearing in the bonding process due to the large area of ​​the first adhesive is relatively small, so it can be set to W2>W3.

[0016] Based on the first aspect, in some possible implementations, the first adhesive component and the second adhesive component are integrally provided.

[0017] Based on the first aspect, in some possible implementations, the first adhesive and the second adhesive are separately arranged; along the second direction, the first adhesive includes a seventh edge and an eighth edge arranged oppositely, and the second adhesive includes a ninth edge and a tenth edge arranged oppositely, and the straight-line distance between the eighth edge and the ninth edge along the second direction is L5, 0≤L5≤5mm. By setting L5≥0, the overlap between the first adhesive and the second adhesive is reduced. If the first adhesive and the second adhesive overlap, the thickness of the overlapping area will increase, affecting the volume energy density of the electrode assembly and the thickness consistency of the electrode assembly in the second direction; by limiting L5≤5mm, the distance between the first adhesive and the second adhesive in the second direction is reduced. If the area of ​​the electrode assembly not covered by the first adhesive or the second adhesive is too large, the risk of the electrode assembly moving in the shell will increase, affecting the anti-drop performance of the electrode assembly. At the same time, the area not covered by the first adhesive or the second adhesive is prone to undervoltage, resulting in a high risk of lithium deposition in the undervoltage area. By limiting 0≤L5≤5mm, it is helpful to reduce the influence of the first adhesive and the second adhesive on the volume energy density of the electrode assembly, improve the risk of lithium plating caused by undervoltage or overvoltage, and improve the anti-drop performance of the electrode assembly.

[0018] Based on the first aspect, in some possible implementations, in the first direction, the thickness of the first adhesive is greater than the thickness of the second adhesive. During hot pressing, the thickness of the first adhesive exceeding the thickness of the second adhesive can be used to compensate for the thickness of the thinned area, so that the gap between the thinned areas of adjacent pole pieces is reduced, and the problem of poor adhesion in the thinned area and easy lithium deposition in the thinned area is improved.

[0019] Based on the first aspect, in some possible implementations, in the first direction, the thickness of the first substrate is greater than the thickness of the second substrate, or the thickness of the first adhesive layer is greater than the total thickness of the second adhesive layer and the third adhesive layer.

[0020] Based on the first aspect, in some possible implementations, in the first direction, the thickness of the first adhesive is T1, the thickness of the second adhesive is T2, and 1.1≤T1 / T2≤2. The thickness ratio of the first adhesive to the second adhesive is within the above range, so that the thickness difference between the first adhesive and the second adhesive is not too small and cannot make up for the thickness difference between the thinning area and the main area, so that the setting of the first adhesive can play a certain role in improving the degree of lithium precipitation in the thinning area; at the same time, the thickness difference between the first adhesive and the second adhesive is not too large, thereby reducing the occurrence of electrolyte infiltration difficulties in the thinning area caused by overpressure at the position covered by the first adhesive, and reducing the occurrence of uneven thickness of the electrode assembly as a whole.

[0021] Based on the first aspect, in some possible implementations, 1.4≤T1 / T2≤1.8, so as to further take into account the poor adhesion of the thinned area, the improvement of the lithium plating problem, and the prevention of overpressure in the thinned area and the thickness uniformity of the electrode assembly.

[0022] Based on the first aspect, in some possible implementations, along the second direction, the width of the thinned area is W1, and 1 mm ≤ W1 ≤ 10 mm.

[0023] Based on the first aspect, in some possible implementations, the electrode assembly further includes an electrode terminal, the extending direction of the electrode terminal is a second direction, and the thinned region extends to an edge of the electrode piece along the second direction.

[0024] A second aspect of the present application provides an electrical device, comprising any one of the above batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a schematic diagram of a battery provided in one embodiment of the present application observed along a first direction.

[0026] Figure 2 for Figure 1 The battery is shown in cross-section along AA.

[0027] Figure 3 A partial schematic diagram of a multi-layer pole piece provided with an adhesive member provided in one embodiment of the present application.

[0028] Figure 4 A partial schematic diagram of a multi-layer pole piece provided with an adhesive is provided for another embodiment of the present application.

[0029] Figure 5 A schematic diagram of an electrode assembly provided with an adhesive member observed along a first direction provided in one embodiment of the present application.

[0030] Figure 6 A schematic diagram of an electrode assembly provided with an adhesive member observed along a first direction provided in another embodiment of the present application.

[0031] Figure 7 A partial schematic diagram of an electrode assembly provided with an adhesive member is provided in yet another embodiment of the present application.

[0032] Figure 8 A schematic diagram of an electrical device provided in accordance with one embodiment of the present application.

[0033] Main component symbols Battery 100 Housing 10 Electrode assembly 20 Electrode terminal 30 Pole piece 21 Main area 21A Thinning area 21B The first gap G1 The second gap G2 First surface 22 First area 22B Second area 22A First adhesive member 41 First substrate 411 First adhesive layer 412 Second adhesive member 42 Second substrate 421 Second adhesive layer 422 The third adhesive layer 423 First edge 41A Second edge 41B Third edge 42A Fourth Edge 42B Fifth Edge 20A Sixth Edge 20B Seventh Edge 41C Eighth Edge 41D Ninth Edge 42C Tenth Edge 42D Positive electrode 220 Positive electrode current collector 221 Positive electrode active material layer 222 Negative electrode 210 Negative electrode current collector 211 Negative electrode active material layer 212 Isolation film 230 Electrical equipment 1 First direction Z Second direction X The third direction Y.

[0034] The following specific implementation methods will further illustrate the present application in conjunction with the above-mentioned drawings. DETAILED DESCRIPTION

[0035] The technical scheme in the embodiment of the present application is described clearly and in detail below. Obviously, the described embodiment is a part of the embodiment of the present application, rather than all the embodiments. Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present application. The terms used in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application.

[0036] Hereinafter, the embodiments of the present application will be described in detail. However, the present application can be embodied in many different forms and should not be construed as being limited to the exemplary embodiments illustrated herein. Rather, these exemplary embodiments are provided so that the present application is thoroughly and in detail communicated to those skilled in the art.

[0037] In addition, for simplicity and clarity, in the accompanying drawings, the size or thickness of various components, layers may be amplified. Throughout the entire text, the same numerical value refers to the same element. As used herein, the term "and / or", "and / or" includes any and all combinations of one or more related enumerated items. In addition, it should be understood that when element A is referred to as "connecting" element B, or element A is referred to as "joining" with element B, element A may be directly connected to element B, or there may be an intermediate element C and element A and element B may be indirectly connected to each other.

[0038] Further, the use of “may” when describing embodiments of the present application means “one or more embodiments of the present application”.

[0039] The technical terms used herein are for the purpose of describing specific embodiments and are not intended to limit the present application. As used herein, the singular form is intended to also include the plural form, unless the context clearly indicates otherwise. It should be further understood that the term "comprising", when used in this specification, refers to the presence of narrated features, values, steps, operations, elements and / or components, but does not exclude the presence or increase of one or more other features, values, steps, operations, elements, components and / or combinations thereof.

[0040] It should be understood that although the terms first, second, third, etc. can be used to describe various elements, components, regions, layers and / or parts herein, these elements, components, regions, layers and / or parts should not be limited by these terms. These terms are used to distinguish one element, component, region, layer or part from another element, component, region, layer or part. Therefore, the first element, component, region, layer or part discussed below can be referred to as the second element, component, region, layer or part without departing from the teachings of the exemplary embodiments.

[0041] See also Figure 1 and Figure 2In one embodiment of the present application, a battery 100 is provided, comprising a housing 10, an electrode assembly 20 and an electrode terminal 30. The electrode assembly 20 is accommodated in the housing 10, and the electrode terminal 30 is connected to the electrode assembly 20 and extends from one side of the housing 10 along a second direction X to connect to an external element. In the present application, the second direction X refers to the length direction of the electrode assembly 20. In the present embodiment, the number of electrode terminals 30 is two, namely a positive terminal and a negative terminal, and the two electrode terminals 30 are located on the same side of the battery 100 in the second direction X. In other embodiments, the number of electrode terminals 30 may be greater than two, and a plurality of electrode terminals 30 may be located on different sides of the battery 100.

[0042] See also Figure 3 , the electrode assembly 20 includes a multilayer electrode sheet 21 stacked along a first direction Z. In the present application, the first direction Z is the thickness direction of the electrode sheet 21, and the first direction Z is perpendicular to the second direction X. The electrode sheet 21 includes a current collector and an active material layer, the active material layer is arranged on at least one surface of the current collector, and the active material layer includes a main region 21A and a thinning region 21B, and the thinning region 21B is connected to the main region 21A and is located at least one edge of the main region 21A. In some embodiments, the main region 21A and the thinning region 21B are arranged in sequence along the second direction X. In the first direction Z, the average thickness T4 of the thinning region 21B is less than the average thickness T3 of the main region 21A, and the first gap G1 between the thinning regions 21B of two adjacent electrode sheets 21 is greater than the second gap G2 between the main regions 21A. In some embodiments, the thickness of the main region 21A is the same, and the thickness of the thinning region 21B decreases in sequence from the main region 21A along the second direction X. In some embodiments, the minimum thickness of the main body region 21A is greater than the maximum thickness of the thinned region 21B.

[0043] See also Figure 2 and Figure 3 The electrode assembly 20 includes a first surface 22 facing the housing 10, and the battery 100 includes an adhesive 40, which bonds the first surface 22 and the housing 10. The area of ​​the first surface 22 overlapping the thinned area 21B in the first direction Z is the first area 22B. The adhesive 40 includes a first adhesive 41. Along the first direction Z, the first adhesive 41 at least partially overlaps with the first area 22B.

[0044] The first adhesive member 41 includes a first substrate 411 and a first adhesive layer 412 stacked along a first direction Z. Along the first direction Z, the surface of the first substrate 411 away from the first adhesive layer 412 covers a portion of the first surface 22, and the surface of the first adhesive layer 412 away from the first substrate 411 adheres to a portion of the housing 10. When the first adhesive layer 412 generates a pulling force with the housing 10 due to its viscosity, the pulling force is not easy to directly act on the first region 22B through the first substrate 411 to increase the first gap G1 between the thinned regions 21B, thereby improving the lithium deposition in the thinned region 21B and the poor adhesion of the pole piece caused by the increase of the first gap G1, thereby improving the cycle performance of the battery.

[0045] In the case where the surface of the first adhesive layer 412 away from the first substrate 411 is bonded to a portion of the housing 10, the surface of the first substrate 411 away from the first adhesive layer 412 may be bonded or not bonded to the portion of the first surface 22 covered by it. In some embodiments, the first substrate 411 includes an adhesive to make the first substrate 411 sticky so that the first substrate 411 is bonded to the first surface 22. The adhesive includes, but is not limited to, one or more of a rubber-based adhesive, a silicone-based adhesive, a water-based adhesive, a polyurethane-based adhesive, an epoxy-based adhesive, and a polyimide-based adhesive.

[0046] In some embodiments, along the first direction Z, the bonding force between the surface of the first substrate 411 away from the first adhesive layer 412 and part of the first surface 22 is F1, and the bonding force between the surface of the first adhesive layer 412 away from the first substrate 411 and part of the shell 10 is F2, 0≤F1≤0.01N / mm, 0.1N / mm≤F2≤1N / mm. When F1 and F2 are within the above range, it is conducive to making it difficult for the pulling force generated between the first adhesive layer 412 and the shell 10 to directly act on the first region 22B through the first substrate 411, so as to increase the first gap G1 between the thinned regions 21B, thereby improving the lithium deposition problem in the thinned regions 21B.

[0047] See also Figure 4 In another embodiment, along the first direction Z, the surface of the first adhesive layer 412 away from the first substrate 411 adheres to a portion of the first surface 22, and the surface of the first substrate 411 away from the first adhesive layer 412 covers a portion of the housing 10. When the adhesive 40 generates a pulling force with the housing 10 due to its viscosity, the pulling force is not easy to directly act on the first region 22B through the first adhesive layer 412 to increase the first gap G1 between the thinned regions 21B, thereby improving lithium deposition in the thinned region 21B caused by the increase in the first gap G1 and improving the cycle performance.

[0048] In the case where the surface of the first adhesive layer 412 away from the first substrate 411 is bonded to a portion of the first surface 22, the surface of the first substrate 411 away from the first adhesive layer 412 and the portion of the housing 10 covered by it may be bonded or not. In some embodiments, the first substrate 411 includes an adhesive to make the first substrate 411 sticky so that the first substrate 411 is bonded to the housing 10. The adhesive includes, but is not limited to, one or more of a rubber-based adhesive, a silicone-based adhesive, a water-based adhesive, a polyurethane-based adhesive, an epoxy-based adhesive, and a polyimide-based adhesive.

[0049] In some embodiments, along the first direction Z, the bonding force between the surface of the first substrate 411 away from the first adhesive layer 412 and part of the housing 10 is F1, and the bonding force between the surface of the first adhesive layer 412 away from the first substrate 411 and part of the first surface 22 is F2, 0≤F1≤0.01N / mm, 0.1N / mm≤F2≤1N / mm. When F1 and F2 are within the above range, it is conducive to making it difficult for the pulling force generated between the adhesive 40 and the housing 10 to directly act on the first region 22B through the first adhesive layer 412, thereby increasing the first gap G1 between the thinned regions 21B.

[0050] In some embodiments, the material of the first substrate 411 includes one or more of polyethylene terephthalate, polyimide, polyethylene, polypropylene, polyvinyl chloride, kraft paper, cotton cloth, synthetic fiber cloth, metal foil, and glass fiber. In some embodiments, the material of the first adhesive layer 412 includes one or more of rubber-based adhesive, silicone-based adhesive, hot melt adhesive, water-based adhesive, polyurethane-based adhesive, epoxy-based adhesive, and polyimide-based adhesive.

[0051] In some embodiments, the housing 10 may be a steel housing, an aluminum housing, a plastic housing (such as polypropylene), a composite metal housing (such as a copper-aluminum composite housing), an aluminum-plastic film or a steel-plastic film, etc. It is understood that when the housing 10 is an aluminum-plastic film or a steel-plastic film, and the first substrate 411 is made of the above polymer, in the hot pressing forming process, the hot pressing temperature is lower than the melting temperature of the polymer in the housing 10 and the first substrate 411, so that the first substrate 411 in the manufactured battery 100 will not be bonded to the housing 10.

[0052] See also Figure 3, along the second direction X, the width of the area where the first adhesive 41 overlaps with the first region 22B is W, and the width of the thinned region 21B is W1. In some embodiments, 0.7≤W / W1≤1.1. When W / W1 is within the above range, it is beneficial to improve the consistency of the thickness of the thinned region 21B at various locations in the second direction X, reduce the risk of undervoltage problems in the thinned region 21B during hot pressing, reduce the risk of lithium precipitation, and improve the cycle performance; it is beneficial to improve the thickness consistency of the thinned region 21B and the main region 21A in the second direction X, reduce the risk of overvoltage problems in the main region 21A during hot pressing, and reduce the risk of lithium precipitation; and the first adhesive 41 has a suitable bonding force with the electrode assembly 20 or the shell 10, which improves the drop resistance of the battery. When W / W1<0.7, the first adhesive 41 is too narrow along the second direction X, and the thickness consistency of the thinned area 21B along the second direction X is poor, which is prone to undervoltage problems, causing lithium deposition; and the bonding force between the first adhesive 41 and the electrode assembly 20 or the shell 10 is insufficient, affecting the drop performance. When W / W1>1.1, the first adhesive 41 is too wide along the second direction X, the first adhesive 41 overlaps with the main area 21A, the thickness of the main area 21A and the thinned area 21B are inconsistent, and the main area 21A is prone to overvoltage, causing lithium deposition; and the overly wide first adhesive 41 will cause the bonding force between the adhesive 40 as a whole and the electrode assembly 20 and the shell 10 to be insufficient, affecting the drop resistance of the battery.

[0053] In some embodiments, 0.8≤W / W1≤1.0, which has a better effect of reducing lithium plating and improving drop performance.

[0054] In some embodiments, the width W1 of the thinned region 21B along the second direction X is 1 mm to 10 mm. For example, W1 is 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm, or a range consisting of any two of these values.

[0055] See also Figure 2 and Figure 3 , the area where the first surface 22 overlaps with the main area 21A in the first direction Z is the second area 22A. In some embodiments, the adhesive 40 includes a second adhesive 42. Along the first direction Z, the second adhesive 42 at least partially overlaps with the second area 22A. The second adhesive 42 includes a second substrate 421, a second adhesive layer 422, and a third adhesive layer 423 stacked along the first direction Z, and the second adhesive layer 422 and the third adhesive layer 423 are arranged on two opposite surfaces of the second substrate 421 along the first direction Z. Along the first direction Z, the second adhesive layer 422 is bonded to the surface of the housing 10 away from the second substrate 421, and the third adhesive layer is bonded to the first surface of the surface away from the second substrate 421.

[0056] In some embodiments, the second substrate 421 includes one or more of polyethylene terephthalate, polyimide, polyethylene, polypropylene, polyvinyl chloride, kraft paper, cotton cloth, synthetic fiber cloth, metal foil, and glass fiber. In some embodiments, the second adhesive layer 422 and the third adhesive layer 423 each include one or more of rubber-based adhesive, silicone-based adhesive, hot melt adhesive, water-based adhesive, polyurethane-based adhesive, epoxy-based adhesive, and polyimide-based adhesive.

[0057] See also Figure 5 , the projection area of ​​the first adhesive 41 along the first direction Z includes a first edge 41A and a second edge 41B that are oppositely arranged along the third direction Y, the projection area of ​​the second adhesive 42 along the first direction Z includes a third edge 42A and a fourth edge 42B that are oppositely arranged along the third direction Y, and the projection area of ​​the electrode assembly 20 along the first direction Z includes a fifth edge 20A and a sixth edge 20B that are oppositely arranged along the third direction Y. The third direction Y is perpendicular to the first direction Z and the second direction X in pairs, and the third direction Y is the width direction of the electrode assembly 20. The first edge 41A, the third edge 42A and the fifth edge 20A are located on the same side of the electrode assembly 20 in the third direction Y, and the second edge 41B, the fourth edge 42B and the sixth edge 20B are located on the other side of the electrode assembly 20 in the third direction Y. The straight-line distance between the first edge 41A and the fifth edge 20A along the third direction Y is L1, the straight-line distance between the second edge 41B and the sixth edge 20B along the third direction Y is L2, the straight-line distance between the third edge 42A and the fifth edge 20A along the third direction Y is L3, and the straight-line distance between the fourth edge 42B and the sixth edge 20B along the third direction Y is L4.

[0058] In some embodiments, 0≤|L1-L2|≤4mm. When the absolute value of the difference between L1 and L2 is within the above range, the first adhesive 41 tends to be located in the middle position of the electrode assembly 20 in the third direction Y, which is beneficial to uniformly distribute the stress applied to the first adhesive 41 by the shell 10 and improve the anti-drop performance.

[0059] In some embodiments, 0≤|L3-L4|≤4 mm. When the absolute value of the difference between L3 and L4 is within the above range, the second adhesive member 42 tends to be located in the middle of the electrode assembly 20 in the third direction Y, which is conducive to uniform distribution of the stress applied by the housing 10 to the second adhesive member 42 and improves the anti-drop performance.

[0060] Along the third direction Y, the length of the first adhesive 41 is W2, the length of the second adhesive 42 is W3, and the width of the projection area of ​​the electrode assembly 20 along the first direction Z in the third direction Y is W4. In some embodiments, 0.5≤W2 / W4≤1. When W2 and W4 are within the above range, the first adhesive 41 has a suitable bonding force with the electrode assembly 20 or the shell 10, which improves the drop performance; and it is beneficial to improve the consistency of the thickness of the thinned area 21B at various locations in the third direction Y, reduce the risk of undervoltage problems in the thinned area 21B during hot pressing, and reduce the risk of lithium precipitation. When W2 / W4<0.5, the first adhesive 41 is too narrow along the third direction Y, and the consistency of the thickness of the thinned area 21B at various locations along the third direction Y is poor, which is prone to undervoltage problems and causes lithium precipitation. When W2 / W4 > 1, the first adhesive member 41 is too wide along the third direction Y, and bubbles may be generated when the first adhesive member 41 is bonded to the electrode assembly 20 , which affects the bonding effect and the drop performance. In some embodiments, 0.6≤W2 / W4≤0.8, which has a better effect on improving lithium plating and drop performance.

[0061] In some embodiments, 0.5≤W3 / W4≤1. When W3 and W4 are within the above range, the second adhesive 41 has a suitable bonding force with the electrode assembly 20 or the shell 10, which improves the drop performance; and it is conducive to ensuring the consistency of the thickness of the main area 21A in the third direction Y, reducing the risk of undervoltage problems in the main area 21A during hot pressing, and reducing the risk of lithium precipitation. When W2 / W4<0.5, the second adhesive 42 is too narrow along the third direction Y, and the consistency of the thickness of the thinned area 21B along the third direction Y is poor, which is prone to undervoltage problems and causes lithium precipitation. When W2 / W4>1, the second adhesive 42 is too wide along the third direction Y, and bubbles may be generated when the second adhesive 42 is bonded to the electrode assembly 20 or the shell 10, affecting the bonding effect and affecting the drop performance.

[0062] In some embodiments, 0.6≤W3 / W4≤0.8, which has a better effect on improving lithium plating and drop performance.

[0063] In some embodiments, W2>W3. Since the width of the thinned region 21B in the second direction X is small, it is not easy to generate bubbles when the first adhesive member 41 covering the thinned region 21B is bonded to the electrode assembly 20 or the housing 10. Therefore, the width of the first adhesive member 41 in the third direction Y can be designed to be greater than the width of the second adhesive member 42 in the third direction Y.

[0064] See also Figure 5 In some embodiments, the first adhesive member 41 and the second adhesive member 42 are separately provided. Along the second direction X, the first adhesive member 41 and the second adhesive member 42 are adjacent to or separated from each other.

[0065] Along the second direction X, the first adhesive 41 includes a seventh edge 41C and an eighth edge 41D that are arranged opposite to each other, and the second adhesive 42 includes a ninth edge 42C and a tenth edge 42D that are arranged opposite to each other. The seventh edge 41C and the ninth edge 42C are located on the same side of the electrode assembly 20 in the second direction X, and the eighth edge 41D and the tenth edge 42D are located on the other side of the electrode assembly 20 in the second direction X. The straight-line distance between the eighth edge 41D and the ninth edge 42C along the second direction X is L5. In some embodiments, 0≤L5≤5mm. When L5 is within the above range, the risk of overlap between the first adhesive 41 and the second adhesive 42 can be reduced, thereby reducing the risk of overpressure caused by overlap; and the area of ​​the adhesive 40 covering the electrode assembly 20 is large enough, which is conducive to improving the drop performance.

[0066] See also Figure 6 In some embodiments, the first adhesive member 41 and the second adhesive member 42 are integrally provided to facilitate processing.

[0067] See also Figure 7 In some embodiments, in the first direction Z, the thickness of the first adhesive 41 is greater than the thickness of the second adhesive 42. During hot pressing, the thickness of the first adhesive 41 exceeding the thickness of the second adhesive 42 can be used to compensate for the thickness of the thinned area 21B, thereby reducing the gap G1 between the thinned areas 21B and improving the lithium deposition problem.

[0068] In some embodiments, in the first direction Z, the thickness of the first substrate 411 is greater than the thickness of the second substrate 421 , so that the thickness of the first adhesive 41 is greater than the thickness of the second adhesive 42 .

[0069] In some embodiments, in the first direction Z, the thickness of the first adhesive layer 412 is greater than the total thickness of the second adhesive layer 422 and the third adhesive layer 423 , so that the thickness of the first adhesive member 41 is greater than the thickness of the second adhesive member 42 .

[0070] See also Figure 4 In some embodiments, the multilayer electrode sheet 21 includes a positive electrode sheet 220 and a negative electrode sheet 210 alternately stacked. The positive electrode sheet 220 includes a positive current collector 221 and a positive active material layer 222 disposed on at least one surface of the positive current collector 221. The negative electrode sheet 210 includes a negative current collector 211 and a negative active material layer 212 disposed on at least one surface of the negative current collector 211. In the process of coating the active material layer slurry to form the active material layer, at the junction of the active material layer slurry and the empty foil area of ​​the current collector, when the active material layer slurry flows toward the edge of the current collector, the volume and flow rate of the active material layer slurry gradually decrease, thereby forming a thinning area 21B.

[0071] In some embodiments, the two outermost layers of the multi-layer pole pieces 21 in the first direction Z have active material layers arranged on a single side, that is, one side of the pole piece has an active material layer arranged on it; the remaining pole pieces are arranged on both sides, that is, the active material layers are arranged on the two opposite sides of the pole pieces along the first direction Z.

[0072] In the first direction Z, the thickness of the first adhesive 41 is T1, and the thickness of the second adhesive 42 is T2. In some embodiments, 1.1≤T1 / T2≤2, and further, 1.4≤T1 / T2≤1.8. When T1 and T2 satisfy the above-mentioned proportional relationship, the thickness of the first adhesive 41 exceeding the second adhesive 42 can compensate for the overall thickness difference of the thinning area 21B, so that the gap G1 between each thinning area 21B is reduced, the effect of improving lithium deposition is better, and the problem of overvoltage in the thinning area and poor uniformity of the overall thickness of the electrode assembly caused by the large difference between T1 and T2 is reduced. Generally speaking, T1 ranges from 27.5μm to 70μm, and T2 ranges from 25μm to 35μm.

[0073] In some embodiments, the positive electrode current collector 221 may be a metal foil or a composite current collector. For example, as the metal foil, aluminum with a silver-plated surface, stainless steel with a silver-plated surface, stainless steel, copper, aluminum, nickel, carbon electrode, carbon, nickel or titanium, etc. may be used. The composite current collector may include a polymer material base layer and a metal layer. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene, polyethylene terephthalate, polybutylene terephthalate, polystyrene, polyethylene, etc.).

[0074] In some embodiments, the positive electrode active material layer 222 may include at least one of the following materials: lithium-containing phosphates, lithium transition metal oxides, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active material layers of batteries may also be used. These positive electrode active material layers may be used alone or in combination of two or more. Among them, examples of lithium-containing phosphates may include, but are not limited to, at least one of lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon. Examples of lithium transition metal oxides may include, but are not limited to, at least one of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and their modified compounds.

[0075] In some embodiments, the negative electrode current collector 211 may be a metal foil, a foamed metal, or a composite current collector. For example, as a metal foil, aluminum or stainless steel treated with silver, stainless steel, copper, aluminum, nickel, carbon electrode, carbon, nickel or titanium, etc. may be used. The foamed metal may be foamed nickel, foamed copper, foamed aluminum, foamed alloy, or foamed carbon, etc. The composite current collector may include a polymer material base layer and a metal layer. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene, polyethylene terephthalate, polybutylene terephthalate, polystyrene, polyethylene, etc.).

[0076] In some embodiments, the negative electrode active material layer 212 may adopt a negative electrode active material layer for a battery known in the art. As an example, the negative electrode active material layer may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active material layers for batteries may also be used. These negative electrode active material layers may be used alone or in combination of two or more.

[0077] See also Figure 4 In some embodiments, the electrode assembly 20 includes a separator 230, which is disposed between the positive electrode sheet 220 and the negative electrode sheet 210. The separator 230 can be any known porous structure separator with good chemical stability and mechanical stability.

[0078] In some embodiments, the electrode assembly 20 is a laminate structure in which the positive electrode sheet 220 , the separator 230 , and the negative electrode sheet 210 are stacked in sequence to form a laminate structure.

[0079] In some embodiments, the electrode assembly 20 is a wound structure in which the positive electrode sheet 220 , the separator 230 , and the negative electrode sheet 210 are stacked in sequence and then wound to form a wound structure.

[0080] In some embodiments, the battery 100 includes an electrolyte, which plays a role in conducting ions between the positive electrode sheet 220 and the negative electrode sheet 210. The electrolyte can be liquid or solid. Among them, the liquid electrolyte includes an electrolyte salt and a solvent, and the solid electrolyte includes a polymer solid electrolyte, an inorganic solid electrolyte, and a composite solid electrolyte.

[0081] In some embodiments, the electrolyte salt may include at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bisfluorosulfonyl imide, lithium bistrifluoromethanesulfonyl imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.

[0082] In some embodiments, the solvent may include at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone. The solvent may also be an ether solvent. The ether solvent may include one or more of ethylene glycol dimethyl ether, ethylene glycol diethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, 1,3-dioxolane, tetrahydrofuran, methyltetrahydrofuran, diphenyl ether and crown ether.

[0083] In some embodiments, the polymer solid electrolyte may be polyether (polyethylene oxide), polysiloxane, polycarbonate, polyacrylonitrile, polyvinylidene fluoride, polymethyl methacrylate, a single ion polymer, polyionic liquid-lithium salt, cellulose, and the like.

[0084] In some embodiments, the inorganic solid electrolyte may include an oxide solid electrolyte (crystalline perovskite, sodium superconducting ion conductor, garnet, amorphous LiPON film), a sulfide solid electrolyte (crystalline lithium superion conductor (lithium germanium phosphosulfide, silver germanium sulfide), amorphous sulfide) and one or more of a halide solid electrolyte, a nitride solid electrolyte and a hydride solid electrolyte.

[0085] In some embodiments, the composite solid electrolyte is formed by adding an inorganic solid electrolyte filler to a polymer solid electrolyte.

[0086] In some embodiments, the shape of the electrode assembly 20 can be cylindrical, flat, polygonal, square, etc.

[0087] See also Figure 8In one embodiment of the present application, there is also provided an electric device 1, comprising any of the above batteries 100. The electric device of the present application may be, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.

[0088] The performance of the battery provided in this application is described below through specific examples and comparative examples.

[0089] Example 1-1 Preparation of positive electrode sheet: The positive electrode active material (lithium cobalt oxide), conductive agent (conductive carbon black), and binder (polyvinylidene fluoride) are dissolved in N-methylpyrrolidone solution at a weight ratio of 97.5:1:1.5 to form a positive electrode active material layer slurry with a solid content of 75wt%. Aluminum foil is used as a current collector, and the positive electrode active material layer slurry is coated on the surface of the positive electrode current collector to obtain a positive electrode active material layer. Subsequently, the positive electrode sheet is obtained by cold pressing and cutting.

[0090] Preparation of negative electrode sheet: negative electrode active material (graphite), conductive agent (conductive carbon black), thickener (sodium carboxymethyl cellulose), binder (styrene-butadiene rubber) are mixed in a mass ratio of 97.5:1:0.5:1, and then deionized water is added as a solvent, and stirred evenly to obtain a negative electrode active material layer slurry with a solid content of 50wt%. Copper foil is used as a current collector, and the negative electrode active material layer slurry is coated on the surface of the negative electrode current collector to obtain a negative electrode active material layer. Then, the negative electrode sheet is obtained by cold pressing and cutting.

[0091] Preparation of diaphragm: Polyethylene film is selected as the diaphragm.

[0092] Preparation of electrolyte: Ethylene carbonate (EC), diethyl carbonate (DEC), propylene carbonate (PC), propyl propionate (PP), and vinylene carbonate (VC) are mixed in a weight ratio of 20:30:20:28:2 to obtain an organic solvent, and then the fully dried lithium salt LiPF6 and the organic solvent are mixed in a weight ratio of 8:92 to obtain an electrolyte.

[0093] Preparation of lithium-ion battery: stack the positive electrode sheet, separator and negative electrode sheet in order, so that the separator is located between the positive electrode sheet and the negative electrode sheet to obtain an electrode assembly; bond the adhesive to the first surface of the electrode assembly, the adhesive includes a first adhesive and a second adhesive, wherein the projection of the first adhesive along the first direction is located in the first area, and the projection of the second adhesive along the first direction is located in the second area; place the electrode assembly in an aluminum-plastic film packaging bag, perform hot pressing bonding at a preset pressure, and obtain a lithium-ion battery after liquid injection and formation. Among them, the first adhesive layer is bonded to the shell.

[0094] Example 1-2 The difference from Example 1-1 is that the first bonding layer bonds the electrode assembly.

[0095] Comparative Example 1 The difference from Example 1-1 is that the first adhesive member also includes a second adhesive layer, and the second adhesive layer bonds the electrode assembly.

[0096] Example 2-1 to Example 2-18 The difference from Example 1-1 is that at least one of W / W1, W2 / W3, W2 / W4, and W3 / W4 is different.

[0097] Example 3-1 to Example 3-9 The difference from Example 1-1 is that at least one of L1-L2, L3-L4, and L5 is different.

[0098] Example 4-1 to Example 4-8 The difference from Example 1-1 is that the value of T1 / T2 is different.

[0099] The test methods for various parameters of this application are described below.

[0100] (1) Thickness test: Division of thinned area and main area: Use an offline laser instrument to measure the thickness of the middle part of the pole piece, and then start from the first test point on the pole piece along the second direction toward the edge of the pole piece to detect the thickness of the pole piece every 0.5mm. When the difference in thickness between two adjacent tests is greater than or equal to 0.01mm, define this point as the dividing point between the main area and the thinned area. Draw a straight line through this point and extend along the third direction. This straight line is the dividing line between the main area and the thinned area.

[0101] In the embodiments and comparative examples of the present application, the thickness of multiple points on the outermost electrode sheet of the electrode assembly is measured to confirm the positions of the thinned area and the main area of ​​the outermost electrode sheet, wherein the outermost electrode sheet is a positive electrode sheet coated with an active material layer on one side.

[0102] Disassemble the battery, take the positive electrode or the negative electrode, select three points in the thinned area from the thinned area toward the main area, use a laser thickness gauge to measure the thickness of the active material layer at the three points, and take the average value to obtain the average thickness of the thinned area.

[0103] Disassemble the secondary battery, take the positive electrode sheet or the negative electrode sheet, select five points in the main area away from the thinning area, use a laser thickness gauge to measure the thickness of the active material layer at the five points, and take the average value to obtain the average thickness of the main area.

[0104] In the embodiments and comparative examples of the present application, the above method is used to measure the thickness of the thinned area and the main area of ​​the outermost electrode sheet of the electrode assembly, wherein the outermost electrode sheet is a positive electrode sheet coated with an active material layer on one side.

[0105] The secondary battery is disassembled, the adhesive components are taken out, and the thickness of the first adhesive component and the second adhesive component are measured by a laser thickness gauge.

[0106] (2) Adhesion test: Disassemble the battery, remove the packaging bag, adhesive and the electrode bonded to the adhesive as a whole, and then cut it into 25mm×25mm strip specimens. Use a peel tester to fix the specimen on the fixture, slowly peel off the adhesive, and measure the force required for peeling. The peeling speed is 50mm / min and the peeling angle is 180°. Calculate the average peeling force and convert the peeling force into bonding force according to the width of the specimen, recorded as F, in N / mm.

[0107] (3) Cycle capacity retention test: At 25°C, charge the lithium-ion battery according to the following charging steps: (1) 1.65C constant current to 4.10V, constant voltage to 1.55C cut-off; (2) 1.55C constant current to 4.20V, constant voltage to 1.4C cut-off; (3) 1.4C constant current to 4.24V, constant voltage to 1.1C cut-off; (4) 1.1C constant current to 4.27V, constant voltage to 0.7C cut-off; (5) 0.7C constant current to 4.30V, constant voltage to 0.4C cut-off; (6) 0.4C constant current to 4.5V, constant voltage to C / 40 cutoff.

[0108] The above charge and discharge process is one cycle. Record the discharge capacity after the first cycle as the initial discharge capacity. Cycle the above charge and discharge process 1000 times, and record the discharge capacity after 1000 cycles as the discharge capacity after the cycle. Capacity retention rate = discharge capacity after cycle / initial discharge capacity × 100%.

[0109] (4) Lithium precipitation test: According to the above charge and discharge process, after repeating 1000 cycles, the battery is disassembled in a fully charged state to obtain the negative electrode sheet adjacent to the outermost single-sided positive electrode, and observe whether there is lithium deposition at the interface of the thinned area of ​​the negative electrode sheet and the ratio of the area of ​​the lithium deposition area to the area of ​​the thinned area of ​​the negative electrode sheet; and observe the ratio of the area of ​​the negative electrode sheet where lithium deposition occurs to the area of ​​the main area of ​​the negative electrode sheet.

[0110] The severity of lithium deposition is analyzed by the ratio of the area of ​​the lithium deposition area to the area of ​​the thinned area of ​​the negative electrode plate, or the ratio of the area of ​​the lithium deposition area to the area of ​​the main area of ​​the negative electrode plate, where no lithium deposition: the lithium deposition area is equal to 0; slight lithium deposition: 0 < lithium deposition area / thinned area area or main area area ≤ 5%; moderate lithium deposition: 5% < lithium deposition area / thinned area area or main area area ≤ 15%; severe lithium deposition: lithium deposition area / thinned area area or main area area > 15%.

[0111] (5) Drop test: The lithium-ion battery was pretreated at 25°C, and after standing for 60 minutes at room temperature, the voltage of the lithium-ion battery before the drop test was tested; the lithium-ion battery was loaded into the fixture, and the drop device was used to freely drop from a position 1.5m above the ground in the following order: head-tail-head right corner-tail right corner-head left corner-tail left corner (angle: 45±15°), and repeated 6 rounds. After the drop, the voltage of the lithium-ion battery was measured and recorded, and the appearance of the lithium-ion battery was checked and photographed before and after the test. The pass criteria for the drop test: no smoke, no leakage, and voltage drop <30mV; among them, the voltage drop test method is to use an internal resistance meter to test the battery voltage before and after the drop, and the voltage drop is the difference between the two. Take 20 samples from each group for drop test, and the drop pass rate = the number of samples that passed the drop test / 20.

[0112] Table 1 It can be seen from the experimental data of Example 1-1 and Comparative Example 1 in Table 1 that, compared with the solution in the prior art in which adhesive layers are provided on both layers of the substrate, the provision of a first adhesive in at least a portion of the first area can reduce the risk of increasing the gap between the outermost electrode and the adjacent diaphragm and deteriorating the adhesion due to the thinning area being pulled, reduce the degree of lithium plating in the thinning area, and improve the cycle performance of the battery.

[0113] Table 2 By comparing the experimental data of Example 1-1 and Example 2-1 to Example 2-6 in Table 2, it can be seen that when 0.7≤W / W1≤1.1, the lithium deposition area of ​​the thinned region is relatively smaller, and the cycle performance of the battery is relatively better; when W / W1<0.7, since the first region is not covered by the first adhesive with a sufficient area, the spacing between the thinned region of the outermost electrode and the adjacent diaphragm is large, which makes the lithium deposition area of ​​the thinned region larger, which has a certain impact on the cycle performance of the battery; when W / W1>1.1, the first adhesive covers part of the second region, which increases the risk of overvoltage in the main region, and the lithium deposition area of ​​the second region increases due to poor electrolyte infiltration, affecting the overall cycle performance of the battery, and the area of ​​the first adhesive is too large, which also affects the anti-drop performance of the battery to a certain extent; in order to take into account the degree of lithium deposition in the thinned region, the degree of lithium deposition in the main region and the anti-drop performance of the battery, it is necessary to limit 0.7≤W / W1≤1.1, and further, 0.8≤W / W1≤1.0 is preferred.

[0114] By comparing the experimental data of Example 1-1 and Example 2-7 to Example 2-12, it can be seen that when the ratio of the width W2 of the first adhesive in the third direction to the width W4 of the electrode assembly in the third direction is 0.5≤W2 / W4≤1, as the ratio W2 / W4 increases, the coverage area of ​​the thinning area by the first adhesive increases, the lithium deposition area of ​​the thinning area gradually decreases, the cycle performance of the battery improves, and the drop resistance of the battery is improved; when W2 / W4<0.5, the thinning area is not sufficiently covered. The first adhesive covering the thinned area leads to a large gap and poor adhesion between the thinned area and the adjacent diaphragm, and the lithium deposition area is larger, which in turn affects the overall cycle performance of the battery. When the area of ​​the first adhesive is too small, the battery has poor anti-drop performance. When W2 / W4>1, the first adhesive has exceeded the width of the electrode assembly in the third direction, which not only causes the size of the electrode assembly in the width direction to become larger, affecting the volume energy density of the battery, but also the adhesive size exceeds the size of the electrode assembly, which affects the anti-drop performance of the battery to a certain extent. Therefore, it is limited to 0.5≤W2 / W4≤1, and further, it is preferably 0.6≤W2 / W4≤0.8.

[0115] By comparing the experimental data of Example 1-1 and Example 2-13 to Example 2-18, it can be known that when the ratio of the width W3 of the second adhesive in the third direction to the width W4 of the electrode assembly in the third direction is 0.5≤W3 / W4≤1, as the ratio W3 / W4 increases, the coverage area of ​​the main area by the second adhesive increases, reducing the undervoltage risk of the main area, the lithium deposition area of ​​the main area gradually decreases, the cycle performance of the battery improves, and the drop resistance of the battery is improved. In addition, compared with the first adhesive, the second adhesive is set as a double-sided tape, and generally speaking, the coverage area of ​​the second adhesive is larger than that of the first adhesive, so W3 / W4 is greater than W2 / The influence of W4 on the anti-drop performance of the battery is more obvious; when W3 / W4<0.5, the main area is not covered by the second adhesive with a sufficient area, resulting in an increased risk of undervoltage in the main area, and a larger lithium deposition area in the main area, which in turn affects the overall cycle performance of the battery. Moreover, if the area of ​​the second adhesive is too small, the electrode assembly is prone to movement relative to the shell, and the battery has poor anti-drop performance; when W3 / W4>1, the second adhesive has exceeded the width of the electrode assembly in the third direction, which not only causes the size of the electrode assembly in the width direction to become larger, affecting the volume energy density of the battery, but also the adhesive size exceeds the size of the electrode assembly, which affects the anti-drop performance of the battery to a certain extent. Therefore, it is limited to 0.5≤W3 / W4≤1, and further, 0.6≤W3 / W4≤0.8 is preferred.

[0116] Table 3 By comparing the experimental data of Example 1-1 and Example 3-1 to Example 3-3 in Table 3, it can be seen that when 0≤|L1-L2|≤4mm, the deviation of the first adhesive in the third direction relative to the center line of the electrode assembly is not large, the lithium deposition area of ​​the thinned region is relatively small, and the battery cycle performance is good; when |L1-L2|>4mm, the deviation of the first adhesive in the third direction relative to the center line of the electrode assembly is large, which can easily cause the adhesion between the thinned area of ​​the outermost electrode and the adjacent diaphragm to deteriorate and the spacing to increase, thereby increasing the lithium deposition area of ​​the thinned area, affecting the battery cycle performance.

[0117] By comparing the experimental data of Example 1-1 and Example 3-4 to Example 3-6, it can be seen that when 0≤|L3-L4|≤4mm, the deviation of the second adhesive in the third direction relative to the center line of the electrode assembly is not large, the lithium deposition area of ​​the main region is relatively small, and the battery cycle performance is good; when |L3-L4|>4mm, the deviation of the second adhesive in the third direction relative to the center line of the electrode assembly is large, which can easily lead to the deterioration of the bonding force and the increase of the spacing between the main region of the outermost electrode and the adjacent diaphragm, thereby increasing the lithium deposition area of ​​the main region and affecting the battery cycle performance; and the second adhesive is not centered relative to the electrode assembly in the third direction, which can easily lead to uneven force on the electrode assembly in the third direction, thereby affecting its anti-drop performance.

[0118] Table 4 By comparing the experimental data of Example 1-1 and Example 4-1 and Example 4-2 in Table 4, it can be seen that when the thickness T1 of the first adhesive is greater than the thickness T2 of the second adhesive, the improvement of the lithium deposition area in the thinning area is more significant. This is because the thickness of the first adhesive exceeding the second adhesive can be used to compensate for the thickness of the thinning area, making the gap between the thinning areas small, and improving the lithium deposition problem in the thinning area. By comparing the experimental data of Example 1-1 and Example 4-3 to Example 4-8, it can be seen that when 1.1≤T1 / T2≤2, the lithium deposition area in the thinning area is small, and the battery cycle performance is better; further, preferably 1.4≤T1 / T2≤1.8. When T1 / T2≥2, the lithium deposition area in the thinning area shows an increasing trend. This is because the difference between the thickness of the first adhesive and the thickness of the second adhesive is large, resulting in overpressure in the thinning area, making it difficult for the electrolyte in the thinning area to infiltrate, thereby causing an increase in the lithium deposition area in the thinning area and a decrease in the battery cycle performance.

[0119] The above disclosure is only a preferred implementation mode of the present application, and certainly cannot be used to limit the scope of rights of the present application. Therefore, equivalent changes made according to the claims of the present application are still within the scope covered by the present application.

Claims

1. A battery, characterized in that: include: case; An electrode assembly is contained in the shell, the electrode assembly comprises a plurality of electrode sheets stacked along a first direction, the first direction being the thickness direction of the electrode sheets; the electrode sheets comprise a current collector and an active material layer, the active material layer being arranged on at least one surface of the current collector; the active material layer comprises a main body region and a thinning region, in the first direction, the average thickness of the main body region is T3, the average thickness of the thinning region is T4, T3>T4; the electrode assembly comprises a first surface facing the shell, the region of the first surface overlapping with the thinning region in the first direction is the first region; as well as An adhesive member, bonding the housing and the first surface, the adhesive member comprising a first adhesive member, the first adhesive member at least partially overlapping the first region along the first direction, the first adhesive member comprising a first substrate and a first adhesive layer stacked along the first direction; Along the first direction, the surface of the first substrate away from the first adhesive layer covers a portion of the first surface, and the surface of the first adhesive layer away from the first substrate adheres to a portion of the housing; or, Along the first direction, a surface of the first adhesive layer away from the first substrate adheres to a portion of the first surface, and a surface of the first substrate away from the first adhesive layer covers a portion of the housing.

2. The battery according to claim 1, characterized in that The material of the first substrate includes one or more of polyethylene terephthalate, polyimide, polyethylene, polypropylene, polyvinyl chloride, kraft paper, cotton cloth, synthetic fiber cloth, metal foil, and glass fiber; the material of the first bonding layer includes one or more of rubber-based adhesive, silicone-based adhesive, hot melt adhesive, water-based adhesive, polyurethane-based adhesive, epoxy-based adhesive, and polyimide-based adhesive.

3. The battery according to claim 1, characterized in that The electrode assembly also includes an electrode terminal, the extension direction of the electrode terminal is a second direction, and the second direction is perpendicular to the first direction; along the second direction, the width of the area where the first adhesive overlaps the first area is W, and the width of the thinned area is W1, 0.7≤W / W1≤1.

1.

4. The battery according to claim 3, characterized in that 0.8≤W / W1≤1.

0.

5. The battery according to claim 1, characterized in that The area of ​​the first surface overlapping with the main body area in the first direction is the second area, the adhesive also includes a second adhesive, along the first direction, the second adhesive at least partially overlaps with the second area, the second adhesive includes a second substrate, a second adhesive layer and a third adhesive layer stacked along the first direction, the second adhesive layer and the third adhesive layer are arranged on two surfaces of the second substrate opposite to each other along the first direction, the surface of the second adhesive layer away from the second substrate is bonded to the shell, and the surface of the third adhesive layer away from the second substrate is bonded to the first surface.

6. The battery according to claim 5, characterized in that The electrode assembly also includes an electrode terminal, the extension direction of the electrode terminal is the second direction, and the third direction is perpendicular to the first direction and the second direction in pairs; observed from the first direction, the first adhesive includes a first edge and a second edge arranged opposite to each other along the third direction, the second adhesive includes a third edge and a fourth edge arranged opposite to each other along the third direction, and the projection area of ​​the electrode assembly along the first direction includes a fifth edge and a sixth edge arranged opposite to each other along the third direction; along the third direction, the fifth edge, the first edge, the second edge, and the sixth edge are arranged in sequence; along the third direction, the fifth edge, the third edge, the fourth edge, and the sixth edge are arranged in sequence; the distance between the first edge and the fifth edge along the third direction is L1, the distance between the second edge and the sixth edge along the third direction is L2, the distance between the third edge and the fifth edge along the third direction is L3, and the distance between the fourth edge and the sixth edge along the third direction is L4; 0≤|L1-L2|≤4mm, and / or, 0≤|L3-L4|≤4mm.

7. The battery according to claim 5, characterized in that The electrode assembly further includes an electrode terminal, the extension direction of the electrode terminal is a second direction, and the third direction is perpendicular to the first direction and the second direction in pairs; Along the third direction, the length of the first adhesive is W2, the width of the second adhesive is W3, the width of the projection area of ​​the electrode assembly along the first direction in the third direction is W4, 0.5≤W2 / W4≤1, and / or, 0.5≤W3 / W4≤1.

8. The battery according to claim 7, characterized in that 0.6≤W2 / W4≤0.8, and / or, 0.6≤W3 / W4≤0.

8.

9. The battery according to claim 7 or 8, characterized in that W2>W3.

10. The battery according to claim 5, characterized in that The first adhesive component and the second adhesive component are integrally provided.

11. The battery according to claim 5, characterized in that The first adhesive member and the second adhesive member are separately provided; the electrode assembly further comprises an electrode terminal, the extension direction of the electrode terminal is a second direction, along the second direction, the first adhesive member comprises a seventh edge and an eighth edge which are arranged opposite to each other, and the second adhesive member comprises a ninth edge and a tenth edge which are arranged opposite to each other; Along the second direction, the seventh edge, the eighth edge, the ninth edge, and the tenth edge are arranged in sequence; the distance between the eighth edge and the ninth edge along the second direction is L5, 0≤L5≤5mm.

12. The battery according to claim 5, characterized in that In the first direction, the thickness of the first adhesive member is greater than the thickness of the second adhesive member.

13. The battery according to claim 12, characterized in that In the first direction, the thickness of the first substrate is greater than the thickness of the second substrate, or the thickness of the first adhesive layer is greater than the total thickness of the second adhesive layer and the third adhesive layer.

14. The battery according to claim 12, wherein: In the first direction, the thickness of the first adhesive member is T1, the thickness of the second adhesive member is T2, and 1.1≤T1 / T2≤2.

15. The battery according to claim 14, characterized in that 1.4≤T1 / T2≤1.

8.

16. The battery according to claim 1, characterized in that The electrode assembly also includes an electrode terminal, the extension direction of the electrode terminal is a second direction, and the second direction is perpendicular to the first direction; along the second direction, the width of the thinned area is W1, 1mm≤W1≤10mm.

17. The battery according to claim 1, characterized in that The electrode assembly further includes an electrode terminal, the extension direction of the electrode terminal is a second direction, and the thinned region extends to an edge of the electrode piece along the second direction.

18. An electrical equipment, characterized in that: Comprising a battery as claimed in any one of claims 1 to 17.

Citation Information

Patent Citations

  • Negative pole piece and secondary battery comprising same

    CN115810718A

  • Secondary battery and electronic device

    CN116722196A

  • Secondary battery, preparation method thereof and electric device

    CN117981109A

  • Negative electrode sheet and secondary battery comprising same

    WO2024109530A1

Cited By

  • Battery and electric device

    WO2026092398A1